Electrical Medical Bed for Disabled People - Jbor, Eyad; Rabee, Shhade (جامعة بوليتكنك فلسطين - اجهزة طبية, 2021)
The project aims to design a smart medical bed that provides adequate comfort for the patient and facilitates treatment for the doctor. It aims to reduce errors in the nature of the patient’s movement, this can be done by adjusting the angles of the head and back areas along with the feet area. The bed consists of two moving platforms and one fixed platform. The moving platforms are supplied with linear actuators to enable the doctor and the patient to control the angular position of these moving platform. The prototype enables the user to control the angular position of each moving platform of the chair remotely or using buttons attached to the chair. The bed can also be converted into a chair to facilitate the transport of the patient to any place he wants depending on four wheels attached to the body of the prototype.
CD, no of pages 65 , اجهزة طبية 5/2021
Keywords: Electrical Medical Bed